Understanding the wear behaviour of non-doped and Si, O-doped diamond-like carbon films. Issue 69 (11th September 2017) - Lanigan, Joseph; Freeman, Helen M.; Wang, Chun; Ward, Michael B.; Morina, Ardian; Neville, Anne; Brydson, Rik
Abstract : Dual mechanisms of wear behaviour of DLCs are explored. One coating shows lower wear, which is partially attributed to the carbon atoms being able to re-hybridize during wearing. Abstract : Two diamond-like carbon coatings have been examined, both prior to, and post tribotesting. Physical–chemical characterisation allows the elucidation of both the physical and tribochemical mechanisms underpinning the respective wear behaviours. The wear of the undoped a-C:H DLC coating is far lower than that of the Si, O-doped DLC. Both coatings show formation of protective tribofilms with tribochemically-relevant elements derived from the lubricant additives; however the tribofilms on the two coatings exhibit key differences, with one containing pyrophosphate. The undoped a-C:H DLC coating shows an increase in non-planar sp 2 carbon content during wear testing which appears to be at the expense of sp 3 -hybridised carbon. In comparison, the Si, O-doped DLC undergoes comparatively little change in carbon hybridisation state.